Observations of the nonstationary atmosphere of the Moon and some its parameters - K. I. Churyumov (Вісник Астрономічної школи, 2012)
Quick increase of brightness of Na D1 and D2 lines in the lunar exosphere during maximum of Perseid 2009 meteor shower on August 13, 2009 at 0-1^h UT is detected and explained by collisions of Perseid meteoroids with the Moon. Total mass of impacted Perseid meteoroids is about 15 kg. Upper limits of intensities of Si, Al, Ca, Fe, Ti, Ba, Li, and Mn lines in the lunar exosphere are estimated.